Peran dan Strategi BKPRMI dalam Meningkatkan SDM Remaja Masjid di Kota Medan - Siti Fitria Soraya; Wildan Ansori Hasibuan; Muhammad Ferdi; Habib Ilmi Nasution (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research discusses the role and strategy of the Indonesian Mosque Youth Communication Agency, abbreviated as (BKPRMI), in improving human resources (HR) for mosque youth in Medan City. BKPRMI is present as a youth organization that focuses on da'wah training, education, economics and character development for the young generation in the mosque environment. This research aims to identify BKPRMI programs, the challenges faced, and solutions in their implementation. The research method uses a qualitative descriptive approach through interviews and literature studies. The research results show that BKPRMI's strategic programs include da'wah management training, faith strengthening studies, economic empowerment, fostering sakinah families, and community health strengthening activities. The main challenges faced by BKPRMI are low youth participation, limited support from mosque administrators, and resistance from the community. However, the solution taken is to approach teenagers through activities that suit their interests and build collaboration with related parties. This research recommends increasing synergy between BKPRMI, the government and the community to strengthen the success of the program.